Impact of covid-19 pandemic on unemployment and Poverty in India: A study - Swati; Prof. S.S. Chauhan (Innovative Research Thoughts, 2021)
Unemployment is a global issue that affects almost every country in the world. In the same way that it's easier to see a giraffe than to explain it, unemployment is difficult to put into words. The unemployment situation has been around for a while now. When it was most severe in industrialised countries, it occurred during the Great Depression of the 1930s; nevertheless, in the emerging countries, “it occurred after the Second World War (1945). In the last several years, job growth in India has slowed, despite a significant increase in the country's economy. Unemployment has skyrocketed in India as a result of the COVID-19 pandemic lockdown”, since most private enterprises have laid off workers. The bulk of workers in the informal sector have been affected by this lockdown, since building has been halted. Thousands of people left their cities and marched for hundreds of kilometres to their homes in the absence of official transportation, expressing their rage at the loss of their capital. COVID-19's influence on unemployment in our research region is the focus of this report. Based on data from books, journals, newspapers and trustworthy online sources we conducted this investigation. Academicians, researchers, and politicians will benefit from this study's findings.